Comparative review of three approaches to biofuel production from energy crops as feedstock in a developing country. (June 2020) - Nikkhah, Amin; El Haj Assad, Mamdouh; Rosentrater, Kurt A.; Ghnimi, Sami; Van Haute, Sam
Abstract: This study is a comparative evaluation of three approaches to biofuel production from energy crops including biogas, bioethanol and biodiesel to ascertain which one is the most effective and more energy-efficient than the others. Moreover, the potential of biofuel production from the best option was studied. For this purpose, biogas generation from corn silage, bioethanol generation from corn, and biodiesel production from peanuts in Iran (as a case study) were studied. The results revealed that 10, 683.36 m 3 of biogas, 2.53 m 3 of bioethanol and 0.70 m 3 of biodiesel could be produced per each hectare of energy crops. The total greenhouse gas emissions for each MJ energy generation of biogas, bioethanol and biodiesel were 0.01, 0.04 and 0.03 kgCO2 eq, respectively. Accordingly, the total annual biogas potential from corn silage (as the best option) in Iran is 3953.74 million m 3, which is equivalent to 1515.94 million barrels of oil. Graphical abstract: Unlabelled Image Highlights: The efficiency of farming some energy crops was studied. Three approaches of biogas, bioethanol, and biodiesel were evaluated. Biogas from corn silage was the most energy efficient way. Atlas of annual potential biogas production from corn silage in Iran was provided.